Features of the special knowledge use in the investigation of murders committed by convicts in prisons - V. V. Kikinchuk; K. H. Mishyna (Law and Safety)
Negative trends in the economy and social relations are slowing down the process of reforming the economic and financial system. The sharp restriction of state control and other negative phenomena that existed in our country have caused a significant increase in crime, especially its organized forms, resulting in a sharp increase in the number of particularly serious crimes against the person. A felony such as murder committed by a convict in prison is no exception.